P692Metabolic control of vessel diameters: vasodilation with low or vasoconstriction with high PO2?. (15th July 2014) - Reglin, B; Pries, AR
Abstract: Purpose: Metabolic regulation of blood flow is needed to match tissue substrate supply to demand. In this process, metabolic signal substances are assumed to act as mediators: decreasing Po2 has been shown to evoke not only increasing release of vasodilators (e.g. NO, adenosine) but also declining release of vasoconstrictors (e.g. HETE). Here, a previously developed model simulation of vascular adaptation was used to compare the suitability for vessel diameter control of vasodilators released in response to declining Po2 with vasoconstrictors which are increasingly released at high Po2. Methods: In the simulation model, all vessels of a rat mesentery microvascular network (576 vessels) change diameter in response to wall shear stress, transmural pressure and local Po2. Local metabolic information is transferred downstream via convection of metabolic signal substances and upstream via conduction along the vessel wall. Information transfer is crucial to prevent shunting. Decreasing levels of local Po2 were assumed to evoke (A) increasing amounts of vasodilators or (B) decreasing amounts of vasoconstrictors. For all conditions tested, model parameters were optimized to achieve lowest deviation between predicted and measured flow velocities (velocity error, VErr). Results: (A) Of all conditions tested, lowest VErr was found for release of substances evoking vasodilation locally, downstream via convection and upstream via conduction assuming oxygen dependence over the full range or restricted to high Po2 levels. (B) Much higher VErr resulted from release of substances evoking vasoconstriction locally, up- and downstream. VErr could be reduced (but not to the VErr level reached by vasodilating effects) by assuming that metabolic signalling evokes vasoconstriction locally but vasodilation up- and downstream. Conclusion: Vasodilators are better suited than vasoconstrictors to metabolically control vessel diameters. The suitability of vasoconstrictors is restricted by the fact that the increase in diameter in response to low Po2 (evoked by low vasoconstrictor release) is partially counteracted by a concentration increase of the vasoconstricting substance in the vessel with decreasing flow ("dilution effect"). Also, for feeding and draining vessels the constrictive signal increases in proportion to the number of capillaries supplied, which is in contrast to the requirements for flow distribution within a vascular network.